PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. BUKADRI VISION BALIKPAPAN - Zea Rahmalita Mawardi Permata Sari; Rahajeng Cahyaning Putri Cipto (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2018)
This study aims to determine the effect of leadership style, work discipline and compensation on employee performance and analyze the dominant variables that affect employee performance at PT. Bukadri Vision Balikpapan. This type of research method is quantitative and uses a sample of 46 people. The results of this study indicate that simultaneous leadership style, work discipline and compensation affect employee performance. Partially, leadership style variables have no effect on employee performance. Work discipline has a positive effect on employee performance. Compensation has no effect on employee performance. Based on these results, the variable that has the most dominant influence is work discipline.Keywords - Leadership Style, Work Discipline, Employee Performance Compensation